Predictors of undergraduate international student psychosocial adjustment to US universities: A systematic review from 2009-2018. (September 2018) - Brunsting, Nelson C.; Zachry, Corinne; Takeuchi, Risa
Abstract: The most recent literature review of predictors of international student adjustment in institutions of higher education in the United States (U.S.) included studies from 1990 to 2009 (Zhang & Goodson, 2011 ). The current review was designed to understand the strengths and gaps of the literature on undergraduate international student adjustment to U.S. universities. Thirty quantitative studies reporting psychosocial outcomes for international undergraduate students at U.S. universities were identified. Acculturative stress, psychological adjustment, social belonging, depression, and anxiety were the most commonly researched outcomes. Recommendations are provided for extension of theoretical frameworks, next steps for researchers, and implications for students, faculty, and staff at U.S. universities.